Preparation of Functional Cookies with Red Grape Pomace Bio-Dust - Sahradyan, S. I.; Ghazaryan, A. V. (ՀԱԱՀ հիմնադրամ)
The influence of secondary raw materials in primary winemaking on the organoleptic and physico-chemical parameters of butter cookies made of wheat and oat flour has been studied. It was revealed that cookies with this additive have appropriate consumer properties and physicochemical parameters that meet accepted standards. It was shown that the processed product was enriched with the elements necessary for the body. These elements include Na, C, Mg, Ca, P, Fe, Zn, and Cu, and the powerful antioxidant resveratrol. Obtaining food additives by processing grape pomace and their use in confectionery products will contribute to primary winemaking with minimal waste.
Keywords: Food Science and Technology